The Impact of Sustainable Sourcing on Halal Certification: A Literature Review on Ethical and Environmental Concerns - Wulandari Sungkowo Tri Putri (Journal of Halal Review, 2025)
Objective: This research analyzes the relationship between halal certification, sustainability, and global ethics in building a resilient and transparent halal supply chain. The focus includes the role of blockchain technology and ESG (Environmental, Social, and Governance) integration to improve traceability, consumer trust, and compliance with sharia and sustainability standards. Research Design & Methods: This research uses a systematic literature review to analyze studies related to halal certification, sustainability, and technology in the halal supply chain. Data were obtained from databases such as Scopus, Web of Science, and Google Scholar. Qualitative analysis was conducted to identify key patterns and practices in sustainable halal supply chain management. Findings: The results show that the integration of blockchain with ESG principles strengthens transparency and traceability at every stage of the halal supply chain, which is crucial in maintaining consumer confidence and compliance with halal standards. Top management commitment and dedicated halal infrastructure also play an important role in ensuring product quality and integrity. In addition, it was found that mandatory halal certification for MSMEs in Indonesia can strengthen the spiritual rights of Muslim consumers, although its impact on improving MSME performance has not been significant without the support of more effective management strategies. Implications & Recommendations: The findings of this study indicate the need for additional strategies, such as subsidizing halal certification, training, and policy support, to strengthen the performance and competitiveness of MSMEs in the international market. In addition, the halal industry is advised to widely adopt blockchain technology and ESG principles as solutions to enhance trust and social responsibility. Contribution & Value Added: This research contributes by offering a framework that integrates blockchain, ESG, and halal certification to build a sustainable halal supply chain. The added value is that it provides insights into the importance of sustainability integration and transparency in the halal industry, strengthens the position of MSMEs in the global market, and supports sustainable development goals.